EKSTRADISI DAN BEBERAPA PERMASALAHANNYA - WARYENTI, DELI (FIAT JUSTISIA)
Extradition is the delivery of an accused or convicted individual who escape to abroad to avoid punishment or trial process. Extradition should be into force whether the two States have made the former treaty related to or based to reciprocity principle. Sometimes, Requested State refuses to surrender the accused person to the Requesting State for many reasons, for example Adrian Kiki who escaped to Australia, but Indonesia could not reach him, although the two States have made a treaty related to. But sometimes, without the treaty of extradition, a State, such as Columbia, surrendered M.Nazaruddin to Indonesia. So basicly, the execution of extradition treaty is uneffective, because it depends on to the good will of the Requested State to do it.Â Â